2021
DOI: 10.1038/s41419-021-03768-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of D-GalN/LPS-induced ALI by 18β-glycyrrhetinic acid through PXR-mediated inhibition of autophagy degradation

Abstract: Acute liver injury (ALI) has multiple causes and results in liver dysfunction. Severe or persistent liver injury eventually leads to liver failure and even death. Pregnane X receptor (PXR)-null mice present more severe liver damage and lower rates of autophagy. 18β-glycyrrhetinic acid (GA) has been proposed as a promising hepatoprotective agent. We hypothesized that GA significantly alleivates D-GalN/LPS-induced ALI, which involved in PXR-mediated autophagy and lysosome biogenesis. We found that GA can signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…The scheme of animal experiments was adapted from that of previous studies ( Zhang et al, 2015 ; Kong et al, 2018 ; Fan et al, 2019 ). The GA dose used here (50 mg/kg) was chosen based on the literature ( Sun et al, 2017 ; Wang et al, 2017 ; Wu et al, 2021 ) and our previous studies. Furthermore, GA at a dose of 50 mg/kg effectively protected against cholestatic liver injury ( Wang et al, 2017 ; Yan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The scheme of animal experiments was adapted from that of previous studies ( Zhang et al, 2015 ; Kong et al, 2018 ; Fan et al, 2019 ). The GA dose used here (50 mg/kg) was chosen based on the literature ( Sun et al, 2017 ; Wang et al, 2017 ; Wu et al, 2021 ) and our previous studies. Furthermore, GA at a dose of 50 mg/kg effectively protected against cholestatic liver injury ( Wang et al, 2017 ; Yan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…PXR has also been shown to regulate liver autophagy and apoptosis pathways, thus having hepatoprotective effects in various liver injuries ( 44 , 45 ). PXR-null mice were reported to have more severe liver damage and suppressed autophagy flow in mice ( 46 ). By using PXR-specific agonist and inhibitor to intervene in autophagy in mice with liver injuries, increasement of the autophagy indexes LC3-B and P62 were observed as a response to agonist pretreatment ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…PXR-null mice were reported to have more severe liver damage and suppressed autophagy flow in mice ( 46 ). By using PXR-specific agonist and inhibitor to intervene in autophagy in mice with liver injuries, increasement of the autophagy indexes LC3-B and P62 were observed as a response to agonist pretreatment ( 46 ). In the present study, pharmacologic activation of PXR by RIF mitigated liver injuries, as shown by the lower levels of hepatocyte vacuolation in the H&E staining.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro and in vivo analysis of GA effects in liver injury revealed that GA increases autophagy by upregulating the LC3-B and P62 autophagy-related genes; however, the autophagy increase mainly relies on the activation of the Pregnane X receptor (PXR), a nuclear receptor involved in metabolism, detoxification, inflammation, oxidative stress. and apoptosis with a significant protective effect on liver, thereby inhibiting the autophagosome–lysosome fusion and blocking the autophagy flux ( Figure 12 ) [ 157 ].…”
Section: Glycyrrhetinic Acidmentioning
confidence: 99%